A review on Phytosome loaded with novel herbal drug and their formulation, standardization and applications - Upase, Amar U; Bhusnure, Omprakash G; Gholve, Sachin B; Giram, Padmaja S; Wattamwar, Pragati B (Journal of Drug Delivery and Therapeutics, 2019)
Novel Drug Delivery System is need of time, as it makes bioavailability, securityand overall therapeutics of a drug easy-going and in the bat of an eye. In the recent days, most of the regnant maladies and nutritional disorders are treated with herbal medicines because of their less after math, economical and easily accessible. The potency of any herbal medication is contingent on the delivery of the effectual level of the therapeutically active constituent. But because of high polarity and poor lipophilicity, the active contents are incompletely assimilated resulting in poor bioavailability.Herbal drugs comprises of a vast array of active contents which furnishes us with a number of applications. But due to high polarity and poor lipophilicity the active contents are poorly absorbed resulting in poor bioavailability. These problems can be overcome by formulating a suitable novel preparation of the herbal extract. Phytosomes are one of the novel drug delivery system containing hydrophilic bioactive phytoconstituents of herbs surround and bound by phospholipids.This phytophospholipid complex resembles a little cell which exhibit better pharmacokinetic and pharmacodynamic profile than the conventional herbal extract resulting in better bioavailability. This article highlights recent information, commercial preparation of phytosomes as well as the various other novel approaches for delivery of herbal constituents.Keywords: Phytosomes, Bioavailability, Phosphatidylcholine, Phytoconstituents.